Bacterial Contamination of Acrylic Resin Complete Denture : In Vitro Study - Al Jmoor, Cheman Abdulrahman (Journal of Baghdad College of Dentistry, 2018)
Background: Cross contamination of dental appliances in the dental clinics and laboratories may potentially be a health hazard to the dental team and the patient. This study aimed to evaluate bacterial contamination of acrylic complete denture as received from dental laboratory before delivery to the patient, and then to evaluate the effectiveness of disinfection with 2% chlorhexidine and Kin denture cleaner tablet.Materials and methods: 45 newly made upper complete dentures undergone biaacterial examination for contamination before delivered to the patient. Samples were examined in two stages, first after finishing and polishing; when collected from the laboratory and before inserting to the patient mouth, second; after the samples were immersed in 2 different disinfectant materials, 2% chlorhexidine mouth wash and Kin denture cleaner tablet. After initial stage, the dentures were divided into 3 groups. Group 1 immersed in Kin denture cleaner tablet for 10 minutes, group 2 immersed in 2% chlorhexidine mouth wash for 10 minutes and group 3 immersed for 20 minutes in 2% chlorhexidine. Data were analyzed with a computer-run statistical program (IBM SPSS Version 23). Results: High score of bacterial contamination was found initially in the sample collected from dental laboratory. Significant reduction in the colonies number was noticed after immersing the dentures in 2% Chlorhexidine and Kin denture cleaner tablets for10 minutes. There was nearly no contamination found with samples immersed in 2% chlorhexidine for 20 minutes. Conclusion: Dental laboratory is a main source of microbial contamination. Immersion of the dental prosthesis in disinfectant materials is essential before inserting into the patient mouth. 2%chlorhexidine mouth wash was more effective as disinfection material as compared to Kin denture cleaner tablet.